Una reflexión necesaria: posibilidad de la construcción de un modelo pedagógico en la educación superior - Castillo Cedeño, Ileana (2008)
The current article presents a series of considerations regarding the significance of establishing a pedagogic model in University level education, as well as its main characteristics, this with the purpose of guiding educational processes towards new and critical perspectives. The article is based on the results of an investigation performed by a team of professionals at the Universidad Nacional.